TRATAMIENTO CONDUCTUAL DE UN CASO DE HIPOCONDRIA - Arabella, Villalobos Crespo (Análisis y Modificación de Conducta, 2023)
A case of hipochondriasis is presented in which i ztensea nd frequent physical sensations appearerl, ar well as avoidance of death and illness related stimuli. Treaiment consisted of anriety reduction, reattibution of physical discomfori and specially bodyfmused intervention and lasted 61 sessions. Several changes were required for the heatment to be effective.